Two distinct DNA ligases from Drosophila melanogaster embryos. - Takahashi, M.; Senshu, M. (FEBS Letters, 1987)
Embryos of Drosophila melanogaster contain two distinct DNA ligases (DNA ligase I and II). DNA ligase I was eluted at 0.2 M KCl and DNA ligase II at 0.6 M KCl on phosphocellulose column chromatography. The former was rich in early developing embryos and its activity decreased during embryonic development. The latter was found constantly throughout the developing stages of embryos. DNA ligase I existed in a cytoplasmic fraction and DNA ligase II is concentrated in nuclei. Both enzymes ligate 5'-phosphoryl and 3'-hydroxyl groups in oligo(dT) in the presence of poly(dA). DNA ligase II is also able to join oligo(dT)(poly(rA). Both enzymes require ATP and Mg2+ for activity. The Km for ATP is 2.7 X 10(-6) M for DNA ligase I, and 3.0 X 10(-5) M for DNA ligase II. DNA ligase I requires dithiothreitol and polyvinyl alcohol, but DNA ligase II does not. Both enzymes are inhibited in the presence of N-ethylmaleimide. DNA ligase I is active at a low salt concentration (0-30 mM KCl), but DNA ligase II is active at high salt concentrations (50-100 mM). DNA ligase I is more labile than DNA ligase II. The molecular masses of DNA ligase-AMP adducts were determined as 86 and 75 kDa for DNA ligase I, and as 70 (major protein) and 90 kDa (minor protein) for DNA ligase II under denaturing conditions. A sedimentation coefficient of 4.2 S was observed for DNA ligase II. Consequently, Drosophila DNA ligase I and II are quite similar to mammalian DNA ligase I and II. Drosophila DNA ligase I and a DNA ligase by B.A. Rabin et al. [(1986) J. Biol. Chem. 261, 10637-10645] seem to be the same enzyme.